The national activity of Mohamed Boudiaf against the French colonization authorities 1946-1954 - Telli, ٌRafik (Journal of Human Sciences, 2022)
This essay deals with the national activity of Mohamed Boudiaf against the French colonization between 1946 and 1954. His struggle started among the Algerian people, then with the Movement for the Triumph of Democratic Liberties party in 1947, in which he worked in to prepare for the revolution of liberation. Boudiaf became the leader of the Organization Union of the Movement for the Triumph of Democratic Libertiesin France after he requested it. However, the party he belongs entered an intense crisis in 1953 between the Messalists and the Centralists; his position remained neutral and worked for reunion and reform between the two which led to his coming back to Algeria at the beginning of March in 1954. Boudiaf tried along with the members of the Revolutionary Committee for Unity and Action to reconcile between the disputing parties, but to no avail. Sir Mohamed Boudiaf initiated his communications with some of theSpecial Organization veterans through holding a set of meetings to take the final arrangements in order to prepare and launch the revolution of liberation on 1st November 1954.